EVALUASI PENYIMPANAN OBAT HIGH ALERT DI RUMAH SAKIT TK. IV GUNTUNG PAYUNG BANJARBARU - Amaliyah Wahyuni; Ade Rita Puspa Negara; Nurmiati Nurmiati (Jurnal Insan Farmasi Indonesia, 2021)
High Alert drugs are drugs that must be watched out for because they often cause serious errors (sentinel events) and drugs that have a high risk of causing Unwanted Drug Reactions (ROTD). The High Alert drug group includes high-risk, look-alike and sound-alike drugs (LASA), and high concentrations. The purpose of this study was to determine the percentage of suitability of High Alert drug storage based on SPO at Tk Hospital. IV Guntung Umbrella Banjarbaru. The type of research used is non-experimental research with descriptive survey research methods. This research was conducted by cross-sectional and the sampling technique used was a saturated sampling technique. The study was conducted at the Tk Hospital. IV Guntung Umbrella Banjarabaru. The research tool used in this study was an observation sheet. The total number of High Alert drugs is (n=70) items, consisting of high-risk drugs (n=22); LASA (Look Alike Sound Alike) (n=45) items; and high concentrate (n=3) items. The results showed the percentage of storage suitability based on the SOP for Tk Hospital. IV Guntung Payung Banjarbaru amounted to 77.14% (54). While the suitability by category, high risk drugs is 72.72% (16), LASA (Look Alike Sound Alike) 77.78% (35), and High Concentrate is 100% (3).